As convenções processuais probatórias na busca do processo efetivo - Petrechen, Mariela Martins Pacheco (2021)
The study proposes to analyze the evidential procedural conventions in the search for ways to achieve effectiveness and process acceleration, placing in balance the role and duties of each subject in the process, focusing on the systematic cooperation, in which the triangular relationship between parties and the judge on an equal footing prevails, in strict compliance with due legal process. The work commences analyzing the fundamental characteristics and norms of contemporary civil process, with which it will be demonstrated that the disciplinary doctrinal dialogue between procedural, constitutional and material law is fundamental for a better interpretation of the letter of our law, always in search for an effective right, of offering judicial protection fairly. Furthermore, as the reduction of the proceedings in progress is still not possible, it is necessary that the scarce resources are optimized so that the available judicial structure can be used in the best way, aiming at a faster and more efficient judicial provision. In this sense, the study encompasses a new technique of the process to obtain the desired procedural effectiveness, which, despite included in article 190 of the Code, is not yet unanimous in Brazilian doctrine. We will analyze requirements such as the nature, validity and effectiveness of procedural conventions. With regard to the central discussion, the purpose of the paper is to address, on the one hand, the autonomy of the parties' will and on the other hand the principles that govern jurisdictional activity, interpreting the law in a systematic way and practicing, whenever necessary, the flexibility of the law. Procedure in favor of its adequacy to material law. Regarding the increase in the cost and time of the judicial activity and in the limitation of the powers of the judge, in the search for a fair solution for the specific case, it is necessary to verify whether or not the party has autonomy to regulate proceedings in matters of test. It is believed that the major discussion revolves around the general negotiation clause on the process: the atypical nature of the evidential procedural convention. The two types of typical conventions in the matter of evidence provided by our coding. Finally, after analyzing the legislation, ideas developed by indoctrinators and understandings presented by our Courts, we will reach the conclusion due to the need for special treatment for procedural conventions, with a focus on those dealing with evidential matters, so that it does not reach the point of making the process unfeasible. The process as a whole, clarifying what law we already have, and it is certain that the Code, more than innovating, chose to clarify some interpretations that should and should be practiced in the light of modern procedural law. Therefore, reaching pertinent conclusions, analyzing vectors, limits for the practice of the evidential procedural conventions and, on the other hand, vectors, limits also for the magistrate's work in all the evidential activity, including in the control of the covenants, will be the main objective of the study